2020
DOI: 10.1002/bmc.4828
|View full text |Cite
|
Sign up to set email alerts
|

The chemical profile of active fraction of Kalimeris indica and its quantitative analysis

Abstract: Kalimeris indica (L) Sch‐Bip is a medicinal plant used by the Miao ethnic group in the Guizhou province of China. It is widely used as a fresh vegetable to treat colds, diarrhea and gastric ulcers. However, few studies have been conducted on the mechanism of its effect on colds, and its quality control. The anticomplement and antitussive activities of different polar extracts of K. indica were evaluated. Fifty‐nine compounds, mainly including phenols and flavonoids, were identified in K. indica extract by ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…MLC primarily contains flavonoids, terpenoids, alkaloids, organic acids, and other chemical constituents. A collection of 133 compounds was gathered from previous literature studies[ 21 - 24 ]. The TCMSP was employed to search for relevant targets of the active ingredients in MLC, resulting in 204 potential targets after duplicate removal.…”
Section: Resultsmentioning
confidence: 99%
“…MLC primarily contains flavonoids, terpenoids, alkaloids, organic acids, and other chemical constituents. A collection of 133 compounds was gathered from previous literature studies[ 21 - 24 ]. The TCMSP was employed to search for relevant targets of the active ingredients in MLC, resulting in 204 potential targets after duplicate removal.…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the quantified marker differences among BCAVA samples from different geographical origins, a heat‐map and HCA analysis were applied to examine the quantitative data (Huang et al, 2020; Wen et al, 2019). Heat maps are the most widely utilized bioinformatic graphic displays for metabolomic data visualization, in which the relative abundance of components detected in each sample is presented through color intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Chinese Pharmacopoeia records that K. indica has the effect of regulating the flow of vital energy, digesting food, and clearing away dampness and heat, and can be used to treat epigastric pain, dysentery, enteritis, urinary tract infection, etc., ( Wang et al, 2010 ; Wang et al, 2015 ; Wang et al, 2017 ). K. indica mainly contains phenolic acids, flavonoids, alkaloids, phytosterols, triterpenoids, volatile oils, polysaccharides, et al ( Lin et al, 2006 ; Ji et al, 2014 ; Ueda et al, 2014 ; Wang et al, 2017 ; Huang, et al, 2020 ). Pharmacological studies showed that it has anti-inflammatory and analgesic, anti-tumor, anti-virus, blood coagulation improving, and other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%